Comparison of Fabrication Techniques for Removable Dentures Using Different Acrylic Resins: A Case Report - Hoaida Shawi; Hajir Alhadi; Rana Qabbasa; Aya Nafda; Ahlam Abu Naama; Zainal Arifin Ahmad (AlQalam Journal of Medical and Applied Sciences, 2025)
Removable dentures are an important service in dentistry for patients due to high access to dentures at a low cost and ease of manufacturing. These prostheses are primarily made from acrylic resin and fall under various types depending on the specific polymerization methods. In this study, we inspected two methods to fabricate maxillary complete dentures using a flasking method (heat cured) and a sprinkle-on method (cold cured). The methods consisted of similar steps before the differences in the methods occurred. The sprinkle-on method certainly demonstrated value due to the great stability of the denture as well as excellent adaptation to the ridge; however, the aesthetic aspect of the denture was poor, especially with the cold-cured acrylic. Furthermore, the cold-cured acrylic had produced some porosity and voids in the denture base. The flasking method was more time-consuming, as it required more equipment; however, the aesthetics of the denture were better and had fewer processing defects.